Antihypertensive and metabolic effects of empagliflozin in Ren-2 transgenic rats, an experimental non-diabetic model of hypertension - Hojná, Silvie; Rauchová, Hana; Malínská, Hana; Marková, Irena; Hüttl, Martina; Papoušek, František; Behuliak, Michal; Miklánková, Denisa; Vaňourková, Zdeňka; Neckář, Jan; Kadlecová, Michaela; Kujal, Petr; et al. (Biomedicine & pharmacotherapy, 2021)
The new antidiabetic drugs, gliflozins, inhibit sodium-glucose transporter-2 in renal proximal tubules promoting glucose and sodium excretion. This leads not only to a significant improvement of glucose control but also to the reduction of blood pressure and body weight in both diabetic patients and experimental models. We examined whether these beneficial effects can also be achieved in a non-diabetic hypertensive model, namely in Ren-2 transgenic rats (TGR). Adult 6-month-old hypertensive TGR and their normotensive controls (Hannover Sprague-Dawley rats), were either untreated or treated with empagliflozin (10 mg/kg/day) for two months. Telemetric blood pressure monitoring, renal parameters as well as cardiac function via echocardiography were analyzed during the experiment. At the end of the study, the contribution of major vasoactive systems to blood pressure maintenance was studied. Metabolic parameters and markers of oxidative stress and inflammation were also analyzed. Empagliflozin had no effect on plasma glucose level but partially reduced blood pressure in TGR. Although food consumption was substantially higher in empagliflozin-treated TGR compared to the untreated animals, their body weight and the amount of epididymal and perirenal fat was decreased. Empagliflozin had no effect on proteinuria, but it decreased plasma urea, attenuated renal oxidative stress and temporarily increased urinary urea excretion. Several metabolic (hepatic triglycerides, non-esterified fatty acids, insulin) and inflammatory (TNF-α, leptin) parameters were also improved by empagliflozin treatment. By contrast, echocardiography did not reveal any effect of empagliflozin on cardiac function. In conclusion, empagliflozin exerted beneficial antihypertensive, anti-inflammatory and metabolic effects also in a non-diabetic hypertensive model.
Keywords: glukosidy; SGLT-2 inhibitor; krevní tlak; hypertenze; Anti-Inflammatory Agents; Glucosides; Renin; Blood Pressure; krysa rodu Rattus; Energy Metabolism; energetický metabolismus; potkani Sprague-Dawley; Antihypertensive Agents; Rats, Transgenic; Benzhydryl Compounds; antioxidancia; antiflogistika; antihypertenziva; Disease Models, Animal; Cardiac; Rats, Sprague-Dawley; mužské pohlaví; hmotnostní úbytek; potkani transgenní; benzhydrylové sloučeniny; Hypertension; zvířata; Weight Loss; Adiposity; Rats; Animals; Renal and metabolic parameters; renin; Male; modely nemocí na zvířatech; Antioxidants; adipozita